Analisa Daya Terima Substitusi Chia Seed Sebagai Pengganti Telur Pada Bahan Pembuatan Mayonnaise Reduced-Fat - Fredericus Hendrich Adolf Gewiess; Lamtiar Hema Malini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mayonnaise is a highly popular type of sauce among the public; however, it contains a high fat content due to its primary ingredients, vegetable oil and eggs. Consequently, mayonnaise has the potential to be developed in terms of its nutritional value. One alternative that can be utilized is replacing eggs with chia seeds, a food ingredient chosen for its ability to serve as a thickener and emulsifier in mayonnaise production. Chia seeds also contain omega-3, fiber, vitamins, and antioxidants that are beneficial for health. The purpose of this study was to reduce the high fat content in mayonnaise so that it can be consumed as a healthier dressing alternative for the wider community. Using the Completely Randomized Design (CRD) method, the substitution ratios of chia seeds to eggs were set at 50:50, 75:25, and 100:0. Data collection methods included organoleptic testing, one-way ANOVA F-test, and laboratory testing (proximate and separated fat analysis) to determine the nutritional content of the mayonnaise. With 25 semi-trained panelists, data collection via questionnaires showed that the highest preference level was achieved by research object P1 (50:50), falling into the